Pengaruh Penggunaan Media Pembelajaran Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Fiqih di MTs. Nahdlatul Ummah Sidoarjo - Afifah Afifah (Universitas Muhammadiyah Jember, 2019)
Learning media constitute an integral part of the learning process in the classroom. To achieve maximum learning outcomes, educators must have knowledge of the management of learning media both as teaching aids and as supporters so that the material/content of the lesson is clearer and can easily be mastered by students. The purpose of this study was to find out how the use of learning media can influence students' learning motivation in Fiqh subjects in MTs. Nahdlatul Ummah Sidoarjo. This paper uses a survey method with a qualitative approach and data collection techniques are observations, interviews and questionnaires. The results of this study concluded that the use of instructional media on the subjects of jurisprudence in MTs. Nahdlatul Sidoarjo Ummah can be said to be quite good, From the results of data analysis shows that the product moment that produces r = 0.758 means that it can be consulted on the product moment interpretation table which is in the interval 0,700-0,900 with an interpretation that between X and Y variables there is a strong correlation